The administration of pirfenidone modifies the expression of JMJD2B in a murine model of NASH - JS Rodriguez Sanabria; J García Bañuelos; R Escutia Gutiérrez; CA Monraz Méndez; A Santos; J Armendáriz-Borunda; AS Sandoval Rodríguez (Annals of Hepatology, 2022)
Introduction and Objectives: This study aimed to evaluate how the administration of pirfenidone modifies the expression of JMJD2B in a murine model of NASH. Materials and methods: 4–5-week-old male C57BL/6J mice fed a high-fat diet for 16 weeks. Follow-up was done at 4, 8, 12 and 16 weeks. Serum glucose, animal weight, caloric intake, AST, ALT, TAG, Chol and VLDL were measured. The liver was weighed, as was the epididymal adipose tissue. Masson's trichrome hematoxylin-eosin staining was performed. Dual-channel microarrays were hybridized to the 22,000-gene version of the Mus musculus genome. Analyzed with adjusted P-values of <0.05 and Z-score values of >1.5 and <1.5 considered significant. Quantitative variables were analyzed with ANOVA, Tukey for parametric data, and Kruskal-Wallis for non-parametric data. The trial was approved by the research ethics committee. Results: The animals achieved the body and biochemical parameters that demonstrate the development of NASH. The genes involved in epigenetic processes responsible for the development of NASH (SIRT1, SIRT2, JMJD1B) and, in particular, in JMJD2B; which found to have significantly different between the HFD vs. HFP and HFD vs. ND groups. Discussion: JMJD2B is a histone methylation modulating enzyme, implicated in the development of NASH. In our trial, pirfenidone modulates the expression of JMJD2B, helping the recovery of liver function through epigenetic regulation in a murine model of NASH. Conclusion: Pirfenidone appears to modulate epigenetic factors, supporting recovery from the disease. Funding: The resources used in this study were from the hospital without any additional financing Declaration of interest: The authors declare no potential conflicts of interest.